Assessment of Electromagnetic Hypersensitivity Syndrome in Subjects Lived Near Mobile Phone Base Station: Gender Based Study - T Ibrahim, Ibrahim; M. Al-Deen, Suad; S.M. Al-Nimer, Marwan; Abdulkareem Yahya, Ali (Diyala Journal of Medicine, 2023)
Background: Electromagnetic hypersensitivity syndrome (EHS) is subjective clinical ‎signs and symptoms caused by exposure to the electromagnetic field. Objective: To show the gender distribution of each category of EHS in people who lived near the mobile ‎phone base station. ‎ Patients and Methods: This cross-sectional study was performed in the College of Medicine, University of Diyala. A total number of 196 individuals (128 men and 68 women) ‎lived within a 1500 m distance away from the mobile phone base station in the Diyala ‎province in the North East of Baghdad-Iraq included in the study. The authors ‎interviewed the participants and completed the EHS questionnaires. Results: Participants reported high scores of sleep disturbances, anxiety, and mood ‎fluctuation compared with other complaints. Men had significantly higher scores of ‎transient deafness and migraine-like headache compared with women. There were no ‎significant differences between men and women with subjective signs and symptoms ‎related to the cardiovascular system or skin. Multi-variable linear regression data ‎revealed a significant correlation (R=0.253) between the total scores of EHS with the ‎age, distance from the base station, and the onset of the illnesses). ‎ Conclusion: We conclude that men who lived in the vicinity of the mobile phone base ‎station are significantly vulnerable to sleep disorder, anxiety, and fluctuation of ‎mood induced by electromagnetic radiation.